Alteration of inflammation cytokines in lipopolysaccharide – activated lymphocyte by crude extract of taurine from sea slug Paraonchidium via down-regulation of NF-kB pathway. Issue 1 (April 2021) - Hafiludin,; Andayani, S; Kartikaningsih, H; Firdaus, M; Mojiono,
Abstract: Free amino acid taurine is found in sea slugs. It has been used as a preventive agent for cardiovascular disease and inflammatory disorders. Inflammation takes place in the presence of lipopolysaccharide (LPS), as a specific inducer, which provokes activation of molecular signals controlling the development of pro-inflammatory and anti-inflammatory cytokines. This current work investigated the effects of taurine extract from shell-less sea slugs on the inhibition of IFN-γ as pro-inflammatory cytokine and IL-10 as anti-inflammatory cytokine in LPS-induced mice lymphocytes. The crude taurine was extracted using water solvent maceration of the sea slug's mucus. Culture of mice splenocytes in RPMI-1640 medium underwent for 5 days and they were then analysed by flow cytometry. As the result, crude taurine extracts substantially suppressed NF-kB expression in T cells, found in all concentrations. The best inhibitory effect was attributed to 500 μg/mL, which was significantly different over control groups (p<0.05). Additionally, the extract inhibited expression of CD4+ IFN-γ + pro-inflammatory cytokines at 500 μg/mL being stronger than inhibition by control (p<0.05), while it improved expression of CD4+IL-10+ anti-inflammatory cytokines at 500 μg/mL compared with control (p<0.05). Our experimental results indicated potential use of taurine crude extract isolated from sea slug Paraonchidium as anti-inflammatory agent from marine source.